2024
DOI: 10.1007/s11469-024-01265-5
|View full text |Cite
|
Sign up to set email alerts
|

Development and Factor Structure of Problematic Multidimensional Smartphone Use Scale

Ekmel Geçer,
Murat Yıldırım,
Hakkı Bağci
et al.

Abstract: Living in an intensifying technological and digital environment makes people more engaged with smartphones and related internet platforms. Alongside its highly debated advantages and disadvantages, modern smartphone use is a global phenomenon which has been mainly debated within the context of cultural and technology relationships which also influence cross-cultural activities. Focusing on one of the modern factors (i.e., smartphone use) that impact human behavior, this article presents the development of a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Multidimensional Smartphone Use Scale (MSUS; [31]). The MSUS is a multidimensional self-report scale aimed at measuring smartphone use in youth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidimensional Smartphone Use Scale (MSUS; [31]). The MSUS is a multidimensional self-report scale aimed at measuring smartphone use in youth.…”
Section: Methodsmentioning
confidence: 99%
“…An example item is "I cannot keep my smartphone away from me" (nomophobia). In the initial developmental study, Geçer et al [31] found that the MSUS exhibited good internal consistency reliability, with Cronbach's alpha coefficients ranging from α = 0.75 to α = 0.89. Furthermore, the factor analytic approach yielded significant evidence supporting the bifactor model, which suggests a single underlying construct (general smartphone use) while simultaneously recognising the multidimensional nature of the construct.…”
Section: Methodsmentioning
confidence: 99%